2017
DOI: 10.1007/s00018-017-2484-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on human adipose-derived mesenchymal stem cells and its potential clinical applications

Abstract: Human adipose-derived mesenchymal stem cells (hASCs) are an ideal cell source for regenerative medicine due to their capabilities of multipotency and the readily accessibility of adipose tissue. They have been found residing in a relatively low oxygen tension microenvironment in the body, but the physiological condition has been overlooked in most studies. In light of the escalating need for culturing hASCs under their physiological condition, this review summarizes the most recent advances in the hypoxia effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 85 publications
1
57
0
Order By: Relevance
“…In fact, our chondrospheroid viability studies revealed larger numbers of dead cells in chondrospheroids cultured in normoxia than in those cultured in hypoxia. These results are in line with those of other authors, who have shown that hASC populations cultured in hypoxia exhibited better growth and survival [39][40][41], with few apoptotic events [17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, our chondrospheroid viability studies revealed larger numbers of dead cells in chondrospheroids cultured in normoxia than in those cultured in hypoxia. These results are in line with those of other authors, who have shown that hASC populations cultured in hypoxia exhibited better growth and survival [39][40][41], with few apoptotic events [17].…”
Section: Discussionsupporting
confidence: 93%
“…In line with this, the microenvironment of hASCs in vivo is also characterized by low oxygen pressure. It has been suggested that hypoxia reduces their potential for osteogenic differentiation [16] while promoting chondral extracellular matrix (ECM) formation [17]. In fact, chondrocyte markers such as SOX9, collagen type II (COL2A1) and aggrecan are positively regulated by hypoxic conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MSC culture at drastically higher atmospheric oxygen levels (21%), most commonly employed in culture protocols, leads to ROS overproduction, DNA damage, and genetic instability compared to culture under physiological oxygen levels (2-8%) [10][11][12][13][14]. Culture under physiological oxygen conditions also leads to increased proliferation and stem cell potency of both pluripotent [15][16][17] and adult stem cells [18][19][20][21][22][23][24]. Although adaptation of culture conditions to physiological oxygen levels to prevent excess ROS is appealing, reducing oxygen levels from atmospheric levels is demanding and pricy and requires specialized equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of hypoxic culture appears interesting, as several of the wound healing properties of ASCs appear to be enhanced [64,65]. Significantly, it was recently found that hypoxic culture of ASCs altered their expression profile of several proteins related to ECM structure and function [66].…”
Section: Using Adipose Stem Cells To Treat Chronic Woundsmentioning
confidence: 99%